MODEL PENGEMBANGAN KECERDASAN MORAL DALAM MENANGGULANGI PERILAKU MENYIMPANG SISWA - Mulyono, Dwi Sri (Sosio Religi: Jurnal Kajian Pendidikan Umum, 2016)
This study was conducted to develop the moral values through moral-based of Civics Learning, with the aims to obtain the factual overview of the implementation of the learning process in schools. This study used a qualitative approach with descriptive methods. The data obtained through observation, interviews, literature studies, and documentation. This study examined the learning programs ranging from the preparation of the planning, implementation, process, and learning outcomes, students displayed through changes in attitudes and behaviors after participating in the learning process. From this study it was found that students were able to show the moral intelligence in schools, families, and communities.